Synthesis of Trimethylolpropane Esters of Calophyllum Methyl Esters : Effect of Temperature and Molar Ratio - Widyawati, Yeti; Suryani, Ani; Romli, Muhammad; Sukardi, Sukardi (International Journal of Renewable Energy Development, 2014)
Trimethylolpropane esters were synthesized by transesterification of calophyllum methyl esters and trimethylolpropane using a calcium oxide as the catalyst. The results showed that the optimal reaction conditions (temperature: 130 0C, reaction time: 5 h, reactant molar ratio: 3.9:1, catalyst amount 3%w/w, and formed trimethylolpropane ester of 79.0% were obtained. The basic physicochemical properties of the trimethylolpropane esters were the following : kinematic viscosities of 56.40 cSt and 8.8 cSt at 40 0C and 100 0C, viscosity index 193, flash point 218 0C and pour point -3 0C. So Methyl esters of fatty acids of would callophylum methyl ester is good raw material for the synthesis of lubricating oils.